Sport, Power, and Identity: Literature Review Tentang Interseksi Politik dan Olahraga - Muhammad Zaidan Barki Muslim; Yuen Cheilo Prasetyo; Himawan Wismanadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study is a literature review that discusses the relationship between sports and politics in historical and contemporary contexts. Through an analysis of 10 recent scientific articles and journals, it was found that sports function not only as physical activities, but also as a tool of diplomacy, a symbol of identity, and a means of political expression. This study identifies various forms of political intervention in sports, both at the institutional level such as FIFA and UEFA, and by countries and individuals such as athletes. In Indonesia, history shows that sports have been a medium for political struggle since the colonial era until now as a tool for imaging and policy diplomacy. This finding emphasizes that sports are not neutral spaces, but strategic arenas in the dynamics of power and global identity. This study provides theoretical and practical contributions in understanding the strategic role of sports in socio-political development and encourages broader interdisciplinary studies in the future.